Investigating how a peer teaching programme could shape the mathematical experience of the participating tutors - Lubasi, Justin Mwandamena (Rhodes University, Faculty of Education, Department of Education, 2015)
This case study, involving six Grade 10 learners, investigates how a peer tutoring programme could shape the mathematical experience and disposition of the participating tutors. The study is grounded in an interpretive paradigm and data was collected in four sequential phases. The Mathematics Dispositional Functions Inventory (MDFI) instrument was completed by the tutors prior to commencement of the tutoring programme. The tutoring sessions then took place over a three week period during which time each tutor kept a reflective journal. Semi-structured interviews were then conducted, after which each tutor completed the MDFI instrument again in order to track any potential changes in their mathematical disposition. The study found that the participating tutors showed an improved mathematics disposition after the peer tutoring experience. Not only was the peer tutoring programme an empowering experience for the tutors, it also had a positive influence on both the tutors' self-confidence as well as their perceived mathematical ability.
Keywords: Mathematics -- Study and teaching (Secondary); Peer teaching; Mathematical ability